2014
DOI: 10.1186/1748-717x-9-42
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated SBRT versus conventionally fractionated EBRT for prostate cancer: comparison of PSA slope and nadir

Abstract: BackgroundPatients with early stage prostate cancer have a variety of curative radiotherapy options, including conventionally-fractionated external beam radiotherapy (CF-EBRT) and hypofractionated stereotactic body radiotherapy (SBRT). Although results of CF-EBRT are well known, the use of SBRT for prostate cancer is a more recent development, and long-term follow-up is not yet available. However, rapid post-treatment PSA decline and low PSA nadir have been linked to improved clinical outcomes. The purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 47 publications
4
26
3
Order By: Relevance
“…In our study, the rate of PSA decline after SBRT was -0.372, -0.211 and -0.128 ng/mL/month for durations of 1, 2 and 3 years, respectively. Although the direct comparison of rate of PSA decline with other study is not proper, the rate of PSA decline in our study tends to be more rapid than that of Anward et al (28) . Shi et al described that a lower PSA at diagnosis had a lower PSA velocity following radiotherapy (21) .…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In our study, the rate of PSA decline after SBRT was -0.372, -0.211 and -0.128 ng/mL/month for durations of 1, 2 and 3 years, respectively. Although the direct comparison of rate of PSA decline with other study is not proper, the rate of PSA decline in our study tends to be more rapid than that of Anward et al (28) . Shi et al described that a lower PSA at diagnosis had a lower PSA velocity following radiotherapy (21) .…”
Section: Discussioncontrasting
confidence: 51%
“…Consistently, in our study, the majority of the PSA decline occurred in the !irst year. Anward et al compared the PSA kinetics between hypofractionated SBRT and conventionally fractionated EBRT for localized prostate cancer and reported that the median slopes for SBRT were -0.09, -0.06 and -0.05 ng/ mL/month, respectively, for durations of 1, 2 and 3 years after radiotherapy (28) . In our study, the rate of PSA decline after SBRT was -0.372, -0.211 and -0.128 ng/mL/month for durations of 1, 2 and 3 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Anwar et al [18] compared the PSA slope between the hypofractionated SBRT and conventionally fractionated external beam radiation therapy (EBRT) for localized prostate cancer and reported that the PSA slope for SBRT was greater than conventionally fractionated EBRT at 2 and 3 years and PSA nadir was significantly lower for SBRT. Katz et al [2] demonstrated that PSA decline steadily after treatment and achieve very low mean levels of 0.25 ng/mL within 4–5 years.…”
Section: Resultsmentioning
confidence: 99%
“…The availability of daily in-room image guidance with techniques such as fiducial markers or in-room CT (cone beam or helical) combined with intensity modulated delivery has facilitated the safe delivery of high dose per fraction using stereotactic body radiotherapy (SABR) techniques. The use of SABR has been described in prostate cancer (42)(43)(44)(45)(46) and has been demonstrated to be safe for treatment of the prostate in phase 1/2 studies. To date, this SABR approach has not been extended to high-risk patients requiring prophylactic treatment of regional nodes, although hypofractionated regional pelvic radiation in other disease sites (ie neoadjuvant rectal cancer) has been shown to be safe and well tolerated (47)(48)(49)(50)(51).…”
Section: Discussionmentioning
confidence: 98%